Culture and Economic Development: Emigration as Evaluation of Lithuanian Cultural Environment - Radavicius, Rytis (Ekonomika, 2016)
This article discusses the influence of culture on economic development and its historical significance. It includes the brief historical analysis of this influence, discussion of problems of its scientific evaluation and presentation of relevant theories and hypotheses. Several practical examples are given that indicate the influence of culture on economy and suggest possible solutions to countries seeking to attain economic welfare. The main issues addressed are: the scope of influence of cultural environment on economic development, the extent of its historical determination and the possibilities to modify it by innovative and consistent actions of the state. The Lithuanian cultural environment is evaluated from an emigration perspective following its comparison with several European countries and the presentation of two qualitative researches carried out by Lithuanian scientists aimed at geographical study preferences of young people.